PENGAWETAN SEPULUH JENIS KAYU SECARA RENDAMAN DINGIN - Emmy Yetty; Barly Barly (Jurnal Penelitian Hasil Hutan, 1990)
The result of cold soaking treatment of ten wood species is reported  in this paper.  Five wood  species are recommended  for housing (agatis, balsa, damar kaca, karet  and  kemayau), whereas  the  other  five  species  (begontoi, belangeran, kenari I, kenari  II and  mahoni) could  not  meet  the  spesification. Solution concentration of Koppers  Formula  7 preservative  used  was 10  percent  with  soaking period  of one, three and five days. The treatment  shchedule  proposed  for five  wood species  is also presented in this  paper.